Social Capital Formation Through Teaching Methods at State Islamic High Schools in Malang - Mokhammad Yahya; Rois Imron Rosi (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
Social capital assumed to be one of the most important aspect which contributed in the societal development of a country. Putnam Analysis proved that the high level of social capital in a country can do so. To form that social capital, all elements in a country need to cooperate each other, including education. Education and social capital produce a very tight connection because the social capital is transmitted in school as an important part of education. This study will explore some teaching methods which can contribute in the formation of social capital in some Islamic high schools in Malang. This study is qualitative in nature. The research subjects were teachers and students in State Islamic High Schools 1 and 2 Malang. The data collection techniques used were interviews, observations, and documentation. The data were analyzed descriptively qualitatively. The results showed that the teachers have practiced some teaching methods that contributed in the social capital element formation of mutual trust, norms, and networking. The social capital formation also formed by the building and developing the productive networking between teachers and students.